Relationship between hyperlipidemia and the risk of death in aneurysm: a cohort study on patients of different ages, genders, and aneurysm locations - Ding, Dianzhu; Yang, Yongbin; Jiang, Guangwei; Peng, Yanhui (Frontiers in Physiology, 2023)
Aims: The study aimed to assess the association of hyperlipidemia and the risk of death in the aneurysm population, focusing on age, gender, and aneurysm location differences. Methods: All patients’ data on this retrospective cohort study were obtained from the Medical Information Mart for Intensive Care (MIMIC-III) database, and the baseline characteristics and laboratory parameters of all patients were collected. The COX regression model was established to explore the association of hyperlipidemia and the risk of death for patients with aneurysms. More importantly, subgroup analyses based on the age, gender, and aneurysm location differences were performed. Results: A total of 1,645 eligible patients were enrolled in this study. These patients were divided into the survival group (n = 1,098) and the death group (n = 547), with a total mortality rate of approximately 33.25%. The result displayed that hyperlipidemia was associated with a decreased death risk in aneurysm patients. In addition, we also found that hyperlipidemia was associated with a lower death risk of abdominal aortic aneurysm and thoracic aortic arch aneurysm among aneurysm patients aged ≥60 years; hyperlipidemia was only a protective factor for the death risk of male patients diagnosed with abdominal aortic aneurysm. For female patients diagnosed with abdominal aortic aneurysm and thoracic aortic arch aneurysm, hyperlipidemia was associated with a decreased death risk. Conclusion: The relationship of hyperlipidemia, hypercholesterolemia, and the risk of death for patients diagnosed with aneurysms was significantly associated with age, gender, and aneurysm location.